Emergenza sanitaria e diritti umani: uno sguardo sul carcere (Società e diritti, 2021)
AbstractIn the context of the measures taken to contain the spread of Covid-19 in places of detention, this contribution analyses the responses of Italy and some European countries, starting from the Interim guidance produced by the WHO, Preparedness, prevention and control of COVID-19 in prisons and other places of detention. Moreover, it compares the measures adopted with the objectives set out in the document, verifying their respect for human rights as a condition for their real effectiveness.